Tumor biology: with a little help from my dying friends - Lauber, Kirsten; Herrmann, Martin (Current Biology, 2015)
Apoptosis is an essential form of cell death underlying daily tissue regeneration. In tumor biology, apoptosis resistance is a well-established hallmark of cancer that is targeted by therapeutic approaches. A new study assigns a hitherto-underestimated function to this 'deadly friend': apoptotic cells promote tumor growth, accumulation of tumor-associated macrophages, and angiogenesis.
EVALuna2:13147